Quality of life and satisfaction after breast augmentation: a systematic review and meta-analysis of Breast-Q patient-reported outcomes - Knoedler, Samuel; Knoedler, Leonard; Kauke-Navarro, Martin; Alfertshofer, Michael; Obed, Doha; Broer, Niclas; Kim, Bong-Sung; Könneker, Sören; Panayi, Adriana C.; Hundeshagen, Gabriel; Kneser, Ulrich; Pomahac, Bohdan; et al. (Journal of plastic, reconstructive & aesthetic surgery, 2024)
Background - Breast augmentation ranks among the most popular plastic surgery procedures. Yet, reports on post-operative patient-reported quality of life (QoL) and satisfaction remain conflicting. - Methods - A systematic review was conducted following the PRISMA guidelines. Three databases were searched for eligible studies that reported pre-and/or post-operative Breast-Q™ augmentation scores for patient QoL (psychosocial, sexual, and physical well-being) and/or satisfaction. - Results - A total of 39 studies (53 patient cohorts and 18,322 patients) were included in the quantitative synthesis. The pairwise meta-analysis revealed significant improvements in patient-reported psychosocial (MD: +38.10) and sexual well-being (MD: +40.20) as well as satisfaction with breast (MD: +47.88) (all p < 0.00001). Physical well-being improved slightly after breast augmentation (MD: +6.97; p = 0.42). The single-arm meta-analysis yielded comparable results, with Breast-Q™ scores in psychosocial and sexual well-being as well as satisfaction with breast increasing from 37.2, 31.1, and 26.3 to 75.0, 70.6, and 72.7, respectively (all p < 0.00001). Physical well-being improved by 8.1 (75.8 pre-operatively to 83.9 post-operatively; p = 0.17). Subgroup analyses highlighted higher QoL and satisfaction following breast augmentation for purely esthetic purposes and alloplastic mammaplasty. Although patient-reported physical and sexual well-being increased in the long term, psychosocial well-being was the highest in the short term. - Conclusion - Patient satisfaction with breast, psychosocial, and sexual well-being increased significantly after breast augmentation. In contrast, patient-reported physical well-being yielded ambivalent results, varying by mammaplasty technique and post-operative follow-up time. Plastic surgeons should be sensitized about our findings to refine eligibility criteria and gain a deeper understanding of the patients’ perceived surgical experience. - Prospero trial registration no - CRD42023409605.